Spatial food‐web structure in the eastern tropical Pacific Ocean based on compound‐specific nitrogen isotope analysis of amino acids. (15th December 2016) - Hetherington, Elizabeth D.; Olson, Robert J.; Drazen, Jeffrey C.; Lennert‐Cody, Cleridy E.; Ballance, Lisa T.; Kaufmann, Ronald S.; Popp, Brian N.
Abstract: The effective evaluation of trophic interactions in pelagic food webs is essential for understanding food web ecology, conservation biology, and management. We tested the applicability of compound‐specific isotope analysis of amino acids (CSIA‐AA) for (1) characterizing trophic positions (TPs) of nine species from four trophic groups (tunas, squids, myctophids, and euphausiids) within a pelagic food web in the eastern tropical Pacific (ETP) Ocean, (2) evaluating trophic discrimination factors (TDFs) of each trophic group, and (3) detecting spatial changes in TPs and food chain length across a region with heterogeneous productivity. Although δ 15 N values of bulk tissues generally increased from south‐to‐north, CSIA‐AA revealed that trophic positions were uniform throughout our study area. These results suggest that variability in δ 15 N values were largely driven by nitrogen cycling dynamics in the ETP, which highlights the importance of these processes for the interpretation of δ 15 N values in food web studies. Absolute TP estimates were unrealistic for higher‐level species, and TDFs (tunas: 4.0‰, squids: 4.6‰, myctophids: 5.0‰, and euphausiids: 7.0‰) were lower than a widely used ecosystem TDF. We used remotely sensed oceanographic data to evaluate the physical oceanography and biological productivity throughout our study area and found significant relationships between δ 15 N values, nitrate concentrations, and SST across our study area. We did not find a gradient in phytoplankton cell size co‐occurring with an expected productivity gradient across our sampling region, which substantiated our isotope results indicating non‐significant spatial changes in TP and food chain length across the ETP.